A use of natural sisal and jute fiber composites for seismic retrofitting of nonductile rectangular reinforced concrete columns. (15th July 2022) - Yooprasertchai, Ekkachai; Wiwatrojanagul, Pongsak; Pimanmas, Amorn
Abstract: Given a size of low-rise residential buildings located in seismic-prone areas, it is difficult to rationalize the application of Carbon Fiber Sheet Polymer (CFRP) sheets for the sake of seismic strengthening. Consequently, this study aimed at finding alternate solutions that could justify the cost without compromising on the performance of strengthened buildings. The potential of sisal and jute fibers was investigated in preventing brittle shear failures of short RC columns. A total of 6 RC columns furnishing typical old non-seismic details with a shear span-to-depth ratio of 2.35 were tested in this study. One column served as control whereas one column was strengthened with 2 layers of CFRP sheets. Rest of the 4 columns were strengthened with 2 and 4 layers of sisal and jute fiber composite sheets. Structural performance in terms of failure modes, ductility, energy dissipation, and peak lateral loads was summarized. It was established that both the natural fiber composites could enhance the structural performance of RC columns to a level comparable to that established by CFRP sheets. This too was achieved by reducing the strengthening cost per column relative to CFRP by 35 and 15% for sisal and jute, respectively. Highlights: Study of Seismic Retrofitting of RC Columns by Natural Fiber Composites. Comparable performance between natural fiber composites and CFRP sheets. Control column failed in shear where all strengthened columns demonstrated sufficient ductility.